The The Linkage Between Problem Solving Skills and Social Attitudes with Environmental Literacy of 10th Grade Students at SMAN 7 Malang - Afifah, Salwa Nabilah; Al Muhdhar, Mimien Henie Irawati; Suhadi, Suhadi; Aisyah, Dini Fithria Nurul; Udiarti, Elly (BIOEDUKASI, 2024)
The link between problem solving skills (X1) and social attitudes (X2) and environmental literacy (Y) is a skill needed by someone to develop attitudes in maintaining a balance between quality of life, environmental quality, and solving environmental problems. This research uses survey research methods. The research design used in this research is a correlational design. The purpose of this study was to determine the linkage between X1 and X2 with Y of 10th grade students at SMAN 7 Malang. This research was conducted at SMAN 7 Malang with 33 respondents from 10th grade students. The analysis of research data using Pearson correlation with a significance value of 0.05. The results of the study obtained an average value of X1 of 55.87, X2 of 79.35, and Y of 69.05. The correlation value of the significance level of X1Y, X2Y, X1X2, X1X2Y is 0.008; 0.951; 0.510; 0.028. The correlation coefficient values of X1Y, X2Y, X1X2, X1X2Y are respectively 0.461; -0.045; -0.119; 0.461. Analysis of the contribution path from X1 provides an effective contribution of 21.34%, X2 provides an effective contribution of -0.045%, while X1X2Y together makes an effective contribution of 21.29%. There is a contribution of 78.71% from other factors (Z). The relationship pattern, suggest that the biggest effective contribution to Y is X1, while X2 must be together with X1 to affect Y effectively.